1981
DOI: 10.1002/ijc.2910280507
|View full text |Cite
|
Sign up to set email alerts
|

Liver cell dysplasia in association with hepatocellular carcinoma, cirrhosis and hepatitis b surface antigen in Hong Kong

Abstract: Liver-cell dysplasia was identified in 60% of 558 cases of cirrhosis with and without hepatocellular carcinoma (HCC) in Chinese coming to necropsy in Hong Kong from 1963 to 1978. A significant correlation was found between liver-cell dysplasia and the identification of hepatitis B surface antigen (HBsAg) in the livers, suggesting that dysplasia may be casually related to hepatitis B virus (HBV). Applying Bayes' theorem to our series of male deaths, we calculated that for Chinese male non-cirrhotics showing liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

1983
1983
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 7 publications
1
10
1
Order By: Relevance
“…There was also a strong relationship between the lesion, male sex, and macronodular cirrhosis and HBs carriage [1]. Similar studies followed from many parts of the world confirming the association of LCC with cirrhosis and HCC [12,[16][17][18][19].…”
Section: The Incidence and Etiology Of Lccmentioning
confidence: 52%
See 1 more Smart Citation
“…There was also a strong relationship between the lesion, male sex, and macronodular cirrhosis and HBs carriage [1]. Similar studies followed from many parts of the world confirming the association of LCC with cirrhosis and HCC [12,[16][17][18][19].…”
Section: The Incidence and Etiology Of Lccmentioning
confidence: 52%
“…In contrast, the incidence is higher in studies on explanted cirrhotic livers, with rates of 71-85% in C viral cirrhosis and 100% in B viral cirrhosis (Table 1) [10][11][12][14][15][16][17][18][19][20]. The substantial increase of LCC in resected specimens may be due to either the occurrence of LCC in the liver adjacent to HCC or to the greater chance of recognizing LCC on larger size specimens as well as at the end-stage of the disease.…”
Section: The Incidence and Etiology Of Lccmentioning
confidence: 58%
“…In keeping with this view are some data from studies carried out in humans, showing that LCD is more frequently observed in patients with HCC than in subjects with other non-neoplastic liver diseases (Anthony et al 1973, Cohen et al 1979, Bartok et al 1981, Ho et al 1981, Roncalli et al 1983). Moreover some chronological evidence supports the hypothesis of a striking connection between LCD and HCC (Anthony et al 1973) and, in addition, it has been shown that the presence of LCD significantly increases the risk of HCC (Ho et al 1981). Figure …”
Section: Discussionmentioning
confidence: 90%
“…LCD is highly associated with HBV [2][3][4][5]; however, it is uncertain whether LCD is morphological pathway in the development of HCC or just habitual feature of HBV-related chronic liver disease, because direct Koo/Seong/Park/Yu/Oh/Oh/Park transformation from LCD to HCC is hard to be evaluated in human liver. HBX transgenic mice that have been used to study hepatocarcinogenesis [21,22] are considered to be a good model to evaluate sequential event from LCD to HCC.…”
Section: Discussionmentioning
confidence: 99%
“…A close relationship between liver cell dysplasia and HBV was observed in areas with high prevalence of HCC and HBV infection [2][3][4][5]. There are two types of liver cell dysplasia, namely the large-cell [6][7][8] and small-cell types, both of which are higher in cirrhotic liver with HCC than those without [8].…”
Section: Introductionmentioning
confidence: 94%